SOSIALISASI PENINGKATAN PEMAHAMAN USAHA MIKRO TERHADAP PERLINDUNGAN KONSUMEN DI KELURAHAN RENON-DENPASAR - Sarjana, I.M.; Priyanto, I.M.D.; Utami, P.D.Y.; Mayasari, I.D.Y.D.; Yogantara, P.; Sukranata, A.A.K.; Indrawati, A.A.S. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana Mengabdi, 2022)
This community service activity aims to provide an understanding of micro business actors that located at Renon, Denpasar about consumer protection law and find out what obstacles are faced by micro business actors in Renon, Denpasar to understanding consumer protection law and to find efforts to overcome obstacles related to increasing micro business in Renon, Denpasar to understanding of consumer protection. The method used in carrying out this activity is the method of distributing brochures and providing education to respondents who were selected by porpusive sampling technique, then followed by discussion, question and answer to obtain results and solutions. The results of this socialization activity indicate that this activity is quite effective to carry out. This can be seen from the enthusiasm of the respondents of micro business actors in Renon, Denpasar to listening the presentation of the service team regarding consumer protection law, especially regarding the rights and obligations of a business actor and consumer. Legal problems that are generally faced by micro business actors in Renon, Denpasar are ignorance of the existence of legal rules that protect consumer rights and regulate business actors and the lack of socialization from the government and related agencies to micro business actors. This activity is carried out by providing education, discussion and question and answer in depth and detail, so that the objectives of this activity can be achieved properly.     Keywords: Understanding, Small Business, Consumer Protection